Bibliometric Analysis of ATAC-Seq and Its Use in Cancer Biology via Nucleic Acid Detection - Zhao, Yu; Zhang, Xianwen; Song, Zhenhua; Wei, Danian; Wang, Hong; Chen, Wei; Sun, Guodong; Ma, Weiying; Chen, Kebing (Frontiers in Medicine, 2020)
Assay for transposase-accessible chromatin using sequencing (ATAC-seq) is associated with significant progress in biological research and has attracted increasing attention. However, the impact of ATAC-seq on cancer biology has not been objectively analyzed. We categorized 440 ATAC-seq publications according to the publication date, type, field, and country. R 3.6.2 was used to analyze the distribution of research fields. VOSviewer was used for country co-authorship and author co-authorship analyses, and GraphPad Prism 8 was used for correlation analyses of the factors that may affect the number of articles published in different countries. We found that ATAC-seq plays roles in carcinogenesis, anticancer immunity, targeted therapy, and metastasis risk predictions and is most frequently used in studies of leukemia among all types of cancer. We found a significantly strong correlation between the top 10 countries in terms of the number of publications and the gross expenditure on research and development (R&D), the number of universities, and the number of researchers. At present, ATAC-seq technology is undergoing a period of rapid development, making it inseparable from the emphasis and investment in scientific research by many countries. Collectively, ATAC-seq has advantages in the study of the cancer mechanisms because it can detect nucleic acids and thus has good application prospects in the field of cancer, especially in leukemia studies. As a country's economic strength increases and the emphasis on scientific research deepens, ATAC-seq will definitely play a more significant role in the field of cancer biology.